Spruce vs. pine did not impact soil organic carbon density but strongly affected a functionally important dwarf shrub in a boreal production forest system - Stein Joar Hegland; Emma E. Olsson; Martin Stensaker; Jakob Gilhuus; Ben Snook; Knut Rydgren; Mark A. K. Gillespie (PLoS ONE, 2025)
In the boreal zone, forestry is one of the most influential drivers of land-use changes. Tree species selection is a management decision which may strongly affect environmental factors that subsequently impact many ecosystem properties including soil carbon storage and functional important species. We used a production forest system in Kaupanger, Western Norway, where Scots pine has been the main timber species and Norway spruce was introduced by forestry. We selected 10 pairs of production stands of spruce or pine with identical productivity index and age for controlled comparison of tree species identity effects on a) soil organic carbon (SOC) density and b) performance of the functionally important bilberry (Vaccinium myrtillus L.). We sampled soil from three depths (5, 15 and 25 cm) at three sampling points per stand for the SOC density analysis, and recorded cover, size, and reproduction of bilberry in five plots per stand. SOC density did not differ significantly between stands of spruce or pine, but pine stands had the highest density of SOC at 5 cm whereas the spruce stands had the highest SOC density at 15 cm depth. The performance of bilberry differed strongly between stand types: the predicted cover of bilberry in pine stands was 47% compared to 5% in spruce stands; the plant size (i.e., dry mass of aboveground ramets) was more than double as large in pine stands; and in spruce stands only one of 50 examined plots had any berries, compared to an almost ubiquitous berry supply in pine stands. Tree species identity appeared to have a neutral effect on the density of SOC in forest soils but had a strong negative effect on all recorded performance variables of the functional important bilberry plant. Spruce stands should be managed for improved light condition to improve habitat quality for dwarf shrubs and its associated biodiversity.